Mixed race in Asia
1 online resource
Keywords: "Mixed racial and ethnic identities are topics of increasing interest around the world, yet studies of mixed race in Asia are rare, despite its particular salience for Asian societies. Mixed Race in Asia seeks to reorient the field to focus on Asia, looking specifically at mixed race in China, Japan, Korea, Indonesia, Malaysia, Singapore, Vietnam and India. Through these varied case studies, this collection presents an insightful exploration of race, ethnicity, mixedness and belonging, both in the past and present. The thematic range of the chapters is broad, covering the complexity of lived mixed race experiences, the structural forces of particular colonial and post-colonial environments and political regimes, and historical influences on contemporary identities and cultural expressions of mixedness. Adding significant richness and depth to existing theoretical frameworks, this enlightening volume develops markedly different understandings of, and recognizes nuances around, what it means to be mixed, practically, theoretically, linguistically and historically. It will appeal to undergraduate and postgraduate students, as well as postdoctoral and other researchers interested in fields such as Race and Ethnicity, Sociology and Asian Studies"--Provided by publisher.